Passing and Ball Control Skills through Small-Sided Games in Futsal Learning at Elementary School Students - Ahmad Mubarak; Hikmad Hakim; Rachmat Kasmad (ETDC: Indonesian Journal of Research and Educational Review, 2026)
This study aimed to examine the effectiveness of the Small-Sided Games (SSG) method in improving sixth-grade elementary school students' passing and ball control skills in futsal, together with its contribution to cognitive and affective learning outcomes. A two-cycle Classroom Action Research (CAR) design following the Kemmis and Taggart model was employed, comprising planning, action, observation, and reflection stages. Cycle I engaged students in homogeneous (male-only) groups, whereas Cycle II involved heterogeneous (male and female) groups with increased training variety and intensity. Learning outcomes were measured through cognitive tests (multiple-choice and short-answer items), direct psychomotor performance assessment of passing and ball control, and structured affective observation. Data were analyzed descriptively by comparing mean scores across the pre-cycle, Cycle I, and Cycle II stages against a success criterion of ≥80. Mean scores increased consistently across cycles. Cognitive scores rose from 62.58 (pre-cycle) to 77.58 (Cycle I) and 87.58 (Cycle II); passing scores from 43.10 to 67.24 and 92.24; ball-control scores from 44.82 to 68.96 and 93.96; and affective scores from 46.55 to 63.79 and 87.06. All indicators exceeded the success threshold by Cycle II, with the largest gains observed in the psychomotor domain. The Small-Sided Games method effectively enhanced students' passing and ball control skills as well as their cognitive and affective learning outcomes by creating a more active, enjoyable, and game-contextual learning environment.